Paul and Scripture - Porter, Stanley E. (1956-) editor; Land, Christopher D., editor (Pauline studies ;, 2019)
"In Paul and Scripture, an international group of scholars discuss a range of topics related to the Apostle Paul and his relationship(s) with Jewish Scripture. The essays represent a broad spectrum of viewpoints, with some devoted to methodological issues, others to general patterns in Paul's uses of Scripture, and still others to specific letters or passages within the traditional Pauline canon (inclusive of the disputed letters). The end result is an overview of the various ways in which Paul the Apostle weaves into his writings the authority, content, and even wording of Jewish Scriptures"--